Siła nabywcza ludności w okręgach uprzemysławianych - Dietl, Jerzy (Wydział Prawa i Administracji UAM, 1968)
This report presents how the purchasing capacity of the population of selected industrial districts in Poland is developing. Attention is drawn to a certain degradation of agriculture in these districts, resulting from a disproportion in agricultural and non-agricultural revenues. The analysis comprises the period between 1951—1965 and some data concerning the years 1966 and 1967. For comparison the area includes a number of districts from various microregions under industrialization. The dynamic and spatial aspects show the global real revenues and income per inhabitant in the districts studied. A clear though differentiated balanced disproportion in the buying capacity per inhabitant is found in the separate districts in relation to the averagje values of the whole country. Note is taken of problems associated with that part of the global revenue which falls on people engaged in socialized economy as well as of the incomes per member in a household. The rate of savings and their influence on the population's consumption fund is also presented.
Purchasing Capacity of Population in Industrialized Districts